Memorable Tourism Experience (MTE) pada Wisatawan di Perkemahan Waduk Sermo - Hakim, Burhan Andi Nur (Gadjah Mada Journal of Tourism Studies, 2023)
Camping has recently gained popularity among tourists. However, research on camping in the Indonesian tourism setting needs to be more extensive, particularly experiential. Sermo Reservoir is a popular camping destination in Kulon Progo Regency, Special Region of Yogyakarta. This study aims to assess tourists’ camping experiences at Sermo Reservoir using Kim et al.’s (2012) Memorable Tourism Experience (MTE) scale. The study included 106 participants recruited through direct surveys of campers who had spent at least one night at Sermo Reservoir in June 2023. A reliability test was performed to determine the internal consistency of the translated scale across all samples. Descriptive quantitative analysis was also performed to determine the level of agreement among Sermo Reservoir camping tourists on each item and dimension of the MTE. The findings revealed that Sermo Reservoir camping tourists agreed on all MTE dimensions at a high to very high level. The characteristics of hedonism and refreshment received a “very high” level of agreement, followed by local culture, novelty, participation, meaningfulness, and knowledge in the “high” agreement category. The study limitations include the adaptation of the scale, which needs to be addressed and investigated further in the local context, and the inclusion of limited acceptance response alternatives. Additional limitations include the short research time, sample procedures, and data collecting, which prevent it from representing MTE in a larger population context.